MODAL SOSIAL PETANI SAWAH BERLAHAN SEMPIT DALAM PEMENUHAN NAFKAH RUMAH TANGGA - Purwito Zanuar Rahmadi; Bambang Santosa (Jurnal Analisa Sosiologi, 2016)
Indoensia is an agricultural country, that agricutural sector hold such important role in the whole national economical aspects. Agricultural lands hold important role in the peasant’s productivity. Agricultural sector in Indonesia experienced high density of labors, meanwhile the quantity space of agricultural is relatively the same, and it’s tend to decreased overtime. This research using case study methods, with purposive sampling where the informant of this research selected by researcher by several considerations. And the subject in this research, the informant, have similarities in propertis and characteristic to each other. Based on the research and the discussion, that social capital small land’s peasant in the household’s fulfillment of living. That peasant with small land, utilized their social capital. With that social capital, small’s land peasant able to carried out the alternative income from source outside beside agricultural activities. Therefore they able to decrease the difficultiness of life in order to fulfill their household living. There’s several alternative source of income that been conducted by peasant in Komomayan Village in order to fulfill their household living by utilizing social capital that peasant’s have i.e livestock, having a debt and cooperation in managing agricultural land.Keywords: Peasant, Social Capital, Household Living. AbstrakIndonesia merupakan negara agraris, bahwa sektor pertanian memegang peranan penting dari keseluruhan perekonomian nasional. lahan pertanian memiliki peranan penting dalam produktifitas petani. Bahwa sektor pertanian mengalami kepadatan tenaga kerja, sementara luas lahan tetap, dan cenderung luas lahan semakin berkurang. Penelitian ini menggunakan metode studi kasus, dengan teknik purposive sampling yaitu informan yang dipilih atau ditentukan secara sengaja oleh peneliti dengan menggunakan pertimbangan tertentu. Serta Informan mimiliki kesamaan dengan sifat atau karakterisitik subjek penelitian ini. Berdasarkan penelitian dan pembahasan, bahwa modal sosial petani sawah berlahan sempit dalam pemenuhan nafkah rumah tangga. Petani sawah berlahan sempit memanfaatkan modal sosial yang dimilikinya. Dengan modal sosial tersebut, petani sawah berlahan sempit mampu menjalankan alternatif pendapatan lain diluar aktifitas bertani, dengan begitu mampu mengurangi kesukaran hidup dalam upaya pemenuhan nafkah rumah tangga. Berbagai alternatif pendapatan yang dilakukan petani sawah di Desa Kolomayan dalam upaya pemenuhan nafkah rumah tangga dengan memanfaatkan modal sosial yang dimilikinya seperti aktifitas beternak, berhutang, dan gotong royong pengerjaan lahan pertanian.Kata Kunci: Petani, Modal Sosial, Nafkah Rumah Tangga.